Wallago Bleeker, 1851 and Wallagonia Myers, 1938 (Ostariophysi, Siluridae), distinct genera of tropical asian catfishes, with description of †wallago maemohensis from the Miocene of Thailand - Tyson R. Roberts (2018)
The Southeast Asian silurid catfish genus Wallagonia Myers, 1938, although regarded as a junior synonym of Wallago Bleeker, 1851 by recent authors following Myers (1948), differs fundamentally from it in many external and osteological characters. The genera evidently have been distinct since at least the middle Miocene and apparently are not closely related to each other. Wallagonia seems most similar to the silurid genus Ompok. Wallago differs most strikingly from all other silurids in having a much longer gape, extending ventroposteriorly well beyond the eyes. The extremely elongate upper jaw has a unique bony composition and suspension. It consists of three bones: the toothed premaxillary bone anteriorly, and the toothless suborbital and first postorbital bones posteriorly. The premaxillary bone is partially suspended from the cranium by the infraorbital bone. The closest relatives of Wallago have not been identified. Wallagonia and Wallago have no previously reported fossil records. Fossils of the family Siluridae have been identified as representatives of the Eurasian temperate genus Silurus (Kobayakawa, 1989). Here an extinct species of Wallago is described, W. maemohensis, on the basis of a complete cranium with attached, fully toothed left premaxillary in an unusually fine state of preservation from a Miocene deposit near Lampang in northern Thailand. Fossil catfishes previously reported from Thailand belong to the families Bagridae and Pangasiidae and are from Pliocene deposits (Roberts and Junmongthai 1999). © 2014 Peabody Museum of Natural History, Yale University. All rights reserved.